The consequences of non-tariff trade barriers: Theory and evidence from import licenses in Argentina - Federico Bernini; Leticia Juárez; Ezequiel García-Lembergman (Inter-American Development Bank (IDB), 2024)
As WTO regulations limited tariffs, non-tariff barriers, such as import licenses (NAILs), became essential trade policy tools. This paper examines how NAILs impact downstream firms in Argentina. Using a novel dataset and the staggered introduction of NAILs between 2005-2011 for identification, we analyze their causal effects on firms' imports and the subsequent effect on exports and employment. Results indicate that NAILs reduce firms' imports, inducing more exposed firms to reduce exports and employment. A trade model with oligopolistic competition suggests that firms' market power can moderate the impact of NAILs in highly concentrated markets.
Keywords: D43; F13; F14; F42; F68; L1; 330; Non-trade barriers; Trade policy; Market power